Diversity of Macrozoobenthos in River Waters around Palaes Waterfall, Likupang Barat District, North Sulawesi - Pontoh, Citra Julia; Saroyo, Saroyo; Papu, Adelfia (International Journal of Biosystem Research, 2026)
Macrozoobenthos are benthic organisms that are highly sensitive to environmental changes and are widely used as bioindicators of river water quality. This study aimed to analyze the species composition and diversity of macrozoobenthos in the Palaes Waterfall River, Likupang Barat, North Sulawesi. Sampling was conducted at three observation stations, namely the waterfall area, plantation area, and residential area, using a Surber net measuring 30 × 30 cm with a mesh size of 500 µm. The collected samples were identified in the laboratory using a stereo microscope and taxonomic identification keys. Community structure was analyzed using the Shannon–Wiener diversity index (H’), Simpson dominance index (D), and Pielou evenness index (E). The results showed that a total of 8 species belonging to 6 families were recorded, with 440 individuals in total. The diversity index (H’) of macrozoobenthos in the Palaes Waterfall River was classified as moderate, with a dominance value of 0.36 and an evenness value of 0.45. These findings indicate that the river ecosystem remains relatively stable and provide essential baseline data for future monitoring and management of water quality in the study area.